Proposal for digital preservation and organization in family archives. Case study: Kati Fond - Martínez de Lahidalga Santillana, Joseba; Marzal García-Quismondo, Miguel Ángel (Revista General de Información y Documentación, 2019)
The aim of this research is based on showing the Kati Family Archive, or Kati Fund, in order to demonstrate the importance of its preservation. Because of the content of his manuscripts is a unique family archive that allows investigating the little-known history of cultural minorities in the Iberian Peninsula and several regions of sub-Saharan Africa. However, if measures to protect the family documentary heritage of natural deterioration and actions of human beings are not considered, the manuscripts are in serious danger of disappearing. Consequently, after explaining the state of the matter of the family archives issue and having described the history of Kati members, the most significant properties of the Kati Fond and its current situation are presented. Then reflect on the measures which provide guarantees for the preservation of the Fond and resolve that digitalization and subsequent preservation in digital repositories is the most effective option for the conservation of the Kati Fond. The research concludes with the proposal for the physical organization of the manuscripts that make up the Fond, focusing on the classification, arrangement and description. It is deemed to employ a classification according to the characteristics of the Fond, a mixed arrangement (alphabetical for the most generic documentary units and chronological for the files) and a description based on the standards proposed by the ICA.